Intra‐ and Interobserver Variability of 4D Ultrasound Examination of the Infrarenal Aorta. (16th January 2021) - Derwich, Wojciech; Wiedemann, Antonia; Wittek, Andreas; Filmann, Natalie; Blase, Christopher; Schmitz‐Rixen, Thomas
Abstract : Objectives: The four‐dimensional ultrasound (4D‐US) enables imaging of the aortic segment and simultaneous determination of the wall expansion. The method shows a high spatial and temporal resolution, but its in vivo reliability is so far unknown for low‐measure values. The present study determines the intraobserver repeatability and interobserver reproducibility of 4D‐US in the atherosclerotic and non‐atherosclerotic infrarenal aorta. Methods: In all, 22 patients with non‐aneurysmal aorta were examined by an experienced examiner and a medical student. After registration of 4D images, both the examiners marked the aortic wall manually before the commercially implemented speckle tracking algorithm was applied. The cyclic changes of the aortic diameter and circumferential strain were determined with the help of custom‐made software. The reliability of 4D‐US was tested by the intraclass correlation coefficient (ICC). Results: The 4D‐US measurements showed very good reliability for the maximum aortic diameter and the circumferential strain for all patients and for the non‐atherosclerotic aortae (ICC >0.7), but low reliability for circumferential strain in calcified aortae (ICC = 0.29). The observer‐ and masking‐related variances for both maximum diameter and circumferential strain were close to zero. Conclusions: Despite the low‐measured values, the high spatial and temporal resolution of the 4D‐US enables a reliable evaluation of cyclic diameter changes and circumferential strain in non‐aneurysmal aortae independent from the observer experience but with some limitations for calcified aortae. The 4D‐US opens up a new perspective with regard to noninvasive, in vivo assessment of kinematic properties of the vessel wall in the abdominal aorta.